2013
DOI: 10.1242/jcs.140764
|View full text |Cite|
|
Sign up to set email alerts
|

Mitoneet mediates TNFα induced necroptosis promoted by fructose and ethanol exposure

Abstract: Fructose and ethanol are metabolized principally in the liver and are both known to contribute to the development of hepatic steatosis that can progress to hepatic steatohepatitis. The present study indentifies a synergistic interaction between fructose and ethanol in promoting hepatocyte sensitivity to TNFa-induced necroptosis. Concurrent exposure to fructose and ethanol induces the overexpression of the CDGSH iron-sulfur domain-containing protein 1 (CISD1 or mitoneet), which is localized to the outer mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…However, this effect was reversed by the pretreatment of the cells with an anti-diabetes agent (pioglitazone) [40]. Taken together, our findings have demonstrated that the combination of alcohol and fructose is able to trigger hepatic IR and diabetes, as well as liver dysfunction in the absence of an increased BW, mostly via synergistic interaction.…”
Section: Discussionmentioning
confidence: 53%
“…However, this effect was reversed by the pretreatment of the cells with an anti-diabetes agent (pioglitazone) [40]. Taken together, our findings have demonstrated that the combination of alcohol and fructose is able to trigger hepatic IR and diabetes, as well as liver dysfunction in the absence of an increased BW, mostly via synergistic interaction.…”
Section: Discussionmentioning
confidence: 53%
“…Many scientists have investigated the regulatory mechanism of necroptosis. Many different molecules were considered to participate in the occurrence and regulation of necroptosis, such as HtrA2/Omi, ubiquitin C-terminal hydrolase (UCH-L1) [ 36 ], CDGSH iron-sulfur domain-containing protein 1 (CISD1) [ 37 ], and calpain [ 38 ]. Of the numerous pathways investigated for their involvement in necroptosis, the RIP signaling pathway was the one that was first studied and gained the most attention.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study demonstrated the relationship between mNT and the inflammatory mediator TNF-α in liver cells [74]. Exposure of primary mouse hepatocytes to fructose and ethanol induced the overexpression of mNT, which primed the cells for TNF-α induced cytotoxicty.…”
Section: Mnt Is Involved In Inflammatory and Metabolic Diseasesmentioning
confidence: 92%